Consumer Satisfaction in E-shopping: Shopee Malaysia Case - Chong, Ming Hui; Chow, Wai Yee; Chow, Xue Qi; Han Lim, Christine Chiaw (Asia Pacific Journal of Management and Education (APJME), 2023)
After the outbreak of the Covid-19 pandemic, e-shopping has grown substantially. Consumer purchasing behavior changed from physical mode to online mode. They comprehended the convenience of purchasing goods on E-shops such as Shopee. Shopee is Malaysia's most popular e-commerce platform, and its user base increased significantly following the pandemic. It created a significant obstacle for Shopee to maintain and enhance consumer satisfaction. Consequently, the purpose of this paper is to discover the factors influencing consumer satisfaction with Shopee in Malaysia. In this study, six factors were identified: perceived ease of use, perceived security, perceived trust, perceived price, and perceived convenience. Our study used an online survey questionnaire created using Google Forms. Through the study, a total of 151 Shopee users from Malaysia were gathered. SPSS will be used to analyze the respondent data to determine the significance of each factor in relation to customer satisfaction. The results of this study show that perceived price, perceived convenience, and perceived security have a significant impact on customer satisfaction. However, perceived ease of use, perceived trust, and perceived usefulness are insignificant in influencing customer satisfaction among Shopee users in Malaysia. This research gives essential information and guidance for enhancing Shopee's customer satisfaction.